Handbook of research on essential information approaches to aiding global health in the one health context - Magalhães, Jorge Lima de; Hartz, Zulmira Maria de Araújo; Jamil, George Leal, 1959-; Silveira, Henrique, 1966-; Jamil, Liliane, 1988- (Advances in data mining and database management (ADMDM) book series., 2022)
"This book studies the management of Big Data in Health information specifically for the new concept "One Health" and "Digital Health", concerning ailments that plague neglected populations and provides practical approaches by scientists and practitioners in the field that will assist in managing the knowledge of Big Data in information Health, to strengthen the skills and training of decision-making managers with tactical and strategic analysis, planning and decision making. This book project aims to"--